Interregional Redistribution and Mobility in Federations: A Positive Approach. - Kessler, Anke S.; Hansen, Nico A.; Lessmann, Christian (Review of Economic Studies, 2011)
The paper studies the effects and the determinants of interregional redistribution in a model of residential and political choice. We find that paradoxical consequences of interjurisdictional transfers arise if people are mobile: while self-sufficient regions are necessarily identical with respect to policies and average incomes in our model, interregional redistribution always leads to the divergence of regional policies and per capita incomes. Thus, interregional redistribution prevents interregional equality. At the same time, however, transfers may allow for more interpersonal equality among the inhabitants of each region. The voting population may therefore in a decision over the fiscal constitution deliberately implement such a transfer scheme to foster regional divergence. Empirical evidence from panel data from OECD countries and Canadian provinces is consistent with the theory. Reprinted by permission of the publisher.